Perempuan dalam Keluarga: Tafsir Ulang Amina Wadud dan Khaled M. Abou El Fadl - Yusuf Setiawan; Subaidi Subaidi (PLEDOI (Jurnal Hukum dan Keadilan), 2023)
The demands of women when they get married is their role in the domestic sphere. A wife's obligation is to take care of children, cook, clean the house, and serve her husband. While earning a living, making connections and relationships, and duties in the public sphere are obligations for the husband. Nowadays, many women are working, educated and have qualifications above men. Meanwhile, the Qur'an and hadith are often used to position and strengthen women in the domestic sphere. So the need to review the sources of Islamic law to adjust the demands of women in this modern era. Amina Wadud as a feminist thinker from among women, has succeeded in interpreting the verses of the Qur'an according to the perspective of female interpreters. While abou al-fadl as a feminist thinker from among men has seen the abuse of hadith interpreted based on the ego of men. This research uses the literature study method. Data was collected and analysed from several references relevant to the topic.. The results of this study, that amina wadud and abou al-fadl reinterpret the position of women in the family sphere, including men and women have equal status, functional differences, Nusyuz is interpreted disharmoniously, divorce, inheritance division, and female witnesses.